Self-esteem and family type in students of a private university in the highlands of Peru - Garcia-Gonzales, Christian Yamil (2022)
Objective: To determine the relationship between the level of self-esteem and the type of family of students from a private university in central Peru. Methodology: This study is basic, of a correlational level, with a non-experimental and cross-sectional design. Applying two questionnaires as instruments, it was carried out in the sample of 34 university students. Results: Regarding the levels of self-esteem in students, with high 44% and 68% have a functional family. Conclusions: Between the variables of level of self-esteem and type of family of the students, it is recognized that there is a significant relationship (p=0.001<0.05).